2020
DOI: 10.1038/s41598-019-57257-2
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Metabolism is Impaired in Overweight Normoglycemic Young Adults without Family History of Diabetes

Abstract: Markers of inflammation and T2DM. Plasma levels of obesity/T2DM related markers [Interleukin 6 (IL-6), C-peptide, Glucagon, Insulin, Leptin, Plasminogen Activator Inhibitor-1 (PAI-1), Resistin, Visfatin, Ghrelin, Glucose-dependent Insulinotropic Polypeptide (GIP), Glucagon-like peptide-1 (GLP-1), and Adiponectin] were measured using Bio-Plex Pro Human Diabetes Assay panel, Bio-Rad, following the manufacturer's protocol 18. A detailed protocol is provided with supplementary materials. plasma sample preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…The results showed that induction of diabetes increased the level of glucose and decreased the level of insulin that are already con rmed by others 1,2,3 . Diabetes destroys β-cells and increases level of glucose and decreases level of insulin.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The results showed that induction of diabetes increased the level of glucose and decreased the level of insulin that are already con rmed by others 1,2,3 . Diabetes destroys β-cells and increases level of glucose and decreases level of insulin.…”
Section: Discussionsupporting
confidence: 76%
“…Beta cells increase insulin secretion for maintaining normal glucose levels and the response is observed as hyperinsulinemia. Patients that hyperinsulinemia cannot maintain normoglycemia, fasting glucose and glucose tolerance are faulted 3 . Defaulted fasting glucose progresses type 2 diabetes mellitus 4 .…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study showed that insulin and C-peptide levels were increased in obese individuals compared to lean controls and suggested obese subjects have an impaired glucose homeostasis and exhibit prediabetic factors, including hyperinsulinemia, and insulin resistance ( 26 29 ). Glucagon levels were elevated in obese individuals ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fasting state stratification highlighted aspects of metabolism which manifest themselves uniquely in the postprandial and fasted states. Indeed, while fasted serum has been a source of many markers for metabolic diseases 36 , individual responses to a meal can carry information regarding metabolic flexibility 37 , prediabetes state 38 or postprandial inflammation 39 . To our knowledge, the issue of the mixed population of fasted and non-fasted subjects in the biobanked samples has not been previously addressed.…”
Section: Discussionmentioning
confidence: 99%